"BA" Guide to Artifacts: Excavated Incense Burners - Fowler, Mervyn D. (The Biblical archaeologist, 1984)
Many objects that have been identified as cultic incense burners were probably nothing of the kind. What are the reasons for and the implications of the misidentification?